Risk investment heuristics: Applied systemic review - Ozorio, D.; Pereira, L.; Gonçalves, R.; Dias, Á.; Lopes da Costa, R. (International Journal of Applied Systemic Studies, 2023)
Investments in projects are judged with rational mathematical parameters. Risky projects can build or destroy companies, careers and fortunes. Being able to fully rationalise the intelligence of the investment judgement seems unlikely. To a greater or lesser extent, cognition interferes with the judges' preference. But would it be possible to identify cognitive traits of the judges' intelligence when deciding on corporate investments? The article makes a systemic literature review of the field on the judgement of corporate investments. The revision suggests that there are gaps in theories about the judgement of corporate investments, which should be solved.